Verification of GPM IMERG data on the total precipitation in Western Siberia in the warm season - Kartavykh, Mikhail S. (Proceedings of SPIE)
This paper presents results of verification of recovered precipitation sums based on GPM IMERG microwave satellite measurements with standard observations at hydrometeorological stations in Western Siberia during summer period. The results revealed good agreement between GPM IMERG data and ground observations at the network of meteorological stations with a correlation coefficient of 0.987. The statistical analysis showed that the average discrepancy between daily precipitation sums according to GPM IMERG data and ground observations for all cases considered is 1.2 mm. The obtained accuracy of GPM IMERG data allows it to be used for most tasks.